A MARKETING BOOKLET FOR THE SQUARE APARTEL & ARCADE: A WAY TO ATTRACT MORE CUSTOMERS TO THE HOTEL - Nadia Natasya Goliat; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
The Square Apartel & Arcade is a new exclusive apartelle (a mixture of apartment and hotel) with a “one stop living” concept. It is located at Siwalankerto Street 146 – 148, Surabaya, East-Java, Indonesia. It is divided into two different types of business; an apartment and a hotel. In reality, many people think that The Square Apartel & Arcade only provides apartments, not lodgings. Therefore, it has become a problem for The Square. To solve this problem, The Square needs a media which can help its owner to show the real business of The Square, i.e. apartment and hotel. As a result, the writer decided to make a marketing booklet which contains eight parts: table of contents, company overview (“About The Square Apartel & Arcade”), product description (“Room Types”), the price of the product (“Room Rates”), additional services, building facilities, shopping arcade, and contact information (“Contact Us”). By having all the information above, prospective customers would have more precise information about the business of The Square. Hopefully, this marketing booklet will enable The Square to attract and get more customers